Implementasi Berpikir Kritis untuk Mempromosikan Konsep Pendidikan Islam dengan Pendekatan Saintifik - Rodhi, Mohammad (Sekolah Tinggi Ilmu Tarbiyah Raden Wijaya Mojokerto, 2019)
During the last decade of the 20th century, the importance of developing children's thinking skills has increased because of the increasing complexity and shift in the reality of modern life increasing the need to produce new knowledge, understanding, assessment and evaluation skills to deal with labor market requirements. In addition, recent critical thinking has become an important qualification demanded by entrepreneurs who are looking for solutions to unexpected problems and strategies to successfully compete in the global business market. Critical thinking is considered the highest intellectual activity in human interaction and allows people to engage in meaningful decision-making processes. the Qur'an speaks of the importance of thinking broadly, which mentions hundreds of times terms such as: Consider (Yaaqilun), understand (yafqahun), learn wisdom (yataffakarun), see (yanzururi), look forward (yubseruri), contemplate (yaat serir), contemplate (yaatabirun), speculate (yatadabbarun), meditate (yaamaluri). This spirit of thinking has marked the Islamic Culture and influenced the way of thinking of Islam which resulted in a prominent character of personal autonomy. This way of thinking emerged clearly in the Islamic tradition in Religion, Philosophy and Science. In understanding Islamic education states that knowledge is relative, cumulative and organized and that scientific theory can only be verified by the facts of reality, and therefore, science education must promote the spirit of inquiry which automatically promotes scientific observation and integrates it with scientific theory in space scope of assumptions and hypotheses. Learning with the scientific approach at school adds to the spirit of inquiry, creativity and objectivity along with aesthetic sensitivity. It aims to develop the ability to know, do and become well-defined.